KONSERVASI SUMBER DAYA ALAM DALAM PERSPEKTIF ISLAM - Syariful Anam, Muhammad; Yulianti, Wina; Nur Safitri, Sari; Nur Qolifah, Siti; Rosia, Rina (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
This study examines how Islam views natural resource conservation. This is a qualitative research with a descriptive approach. Based on the results of the studies that have been carried out, it can be concluded that Islam teaches humans to be responsible for all of Allah's creation, including being responsible for protecting and maintaining natural resource ecosystems. The principle of conservation in Islam is based on mutual care between humans and nature, because basically humans take advantage of the available natural resources. In addition, in the utilization of natural resources, humans must pay attention to balance, not be exploitative and remain proportional so that natural resources are preserved.